Determinants of international Muslim tourists’ empowerment and attitude, and their impact on loyalty - Ab Hamid, Siti Halimah (2018)
Good continuation of tourist loyalty could ensure sustainability in tourism industry, thus the study of consumer behaviour including empowerment, attitude and loyalty is vital in order to understand their needs. One market segment that is on the rise and could provide economic opportunities is the Muslim tourists. The question is whether the tourism industry in Malaysia has provided sufficient tourism facilities to gain the loyalty of Muslim tourists. Malaysia possesses many attributes of Halal tourism but several issues could hinder the sector such as unclear standards and rules. Besides, there are other general issues, such as bad reviews on the tourism resources, slow communication and lack of innovation in tourism products that may affect tourists’ behaviour. Therefore, with the support of Theory of Planned Behaviour (TPB) and Information Integration Theory (IIT), the research aims to examine the relationships between Halal tourism brand equity (HTBE), integrated marketing communication (IMC), destination competitiveness (DC) and destination innovation (DI) mediated by Muslim tourists’ empowerment (EMP) and attitude (ATT) with the final impact on loyalty (LOY). 456 questionnaires were collected from the international Muslim tourists around Kuala Lumpur. The data was analysed using SPSS and Structural Equation Modelling in AMOS. The results suggested that there are significant relationships between HTBE and IMC on EMP, DC and DI on ATT, EMP on ATT and ATT on LOY. Besides, EMP mediates the relationship between HTBE and IMC with ATT. While ATT mediates the relationship between DI and EMP with LOY but not between DC with LOY. The research has extended the body of knowledge in TPB, IIT and consumer behaviour study. There are practical implications to the practitioners and the policy makers where they could focus and strategized on the determinants that would strengthen the competitiveness of Malaysia as a destination and ensure the continuity and sustainability of the tourism industry.